Análisis del método de TSC para la obtención de la DOS en materiales semiconductores. - Dussan, A. (MOMENTO, 2006)
In this work, a detailed study of thermally stimulated con- ductivity technique (TSC) is presented. Density of states (DOS) was obtained from the experimental measurements on boron-doped microcrystalline silicon samples [μc-Si:H (B)] and compared with results obtained by the modula- ted photoconductivity methods. To explain the poor agree- ment between the DOS obtained from the TSC and the other methods, it is shown by means of numerical simula- tions that the DOS is very sensitive to experimental errors introduced in the calculation of the μnτn product (mobility of electron × lifetime of the electron).